Challenges to sexual health information seeking behaviour among adolescents in Nigeria (2014)
This paper discusses the factors affecting the development of young people and their reproductive and sexual health. It reviews literature on the behaviour of young people vis a vis their reproductive and sexual risk behaviours such as low knowledge of contraception, high infection rate, early sexual initiation, early child bearing, unsafe abortion and lack of Information on STIs and HIV/AIDS. The health belief model was used as a basis to examine whether young people consider their health as important in their daily decision in relation to the issue of sexual activity. The paper also examines the relevance of Erikson’s stages of psychosocial development which deals with how children socialize and how this affects their sense of self. The paper sums up documented studies on the poor health-seeking behaviours of young people which is the bases for their continuous risky behaviour. It finally argues that poor information seeking behaviour among young people could be based on cultural and traditionalvalues that prevent information seeking on sexual issues. It then recommends that reliable information should be disseminated through public health campaigns, the media, and the educational system.